Lack of Torsion in the Type-III Duane Retraction Syndrome (DRS-III) Affected Left Eye During Dix -Hallpike Test - Vats, Ajay Kumar (Annals of Otology and Neurotology, 2020)
Background Duane retraction syndrome (DRS) is a congenital cranial dysinnervation disorder (CCDD) of ocular movements, characterized by deficits in horizontal duction associated with narrowing of palpebral fissure, retraction of eye globe on attempted adduction and occasionally accompanied by upshoot or downshoot of the eye globe. It is caused by congenital absence of sixth cranial nerve, which results in fibrotic changes in the extraocular muscles leading to an abnormal ocular motility--a concept known as CCDD. Depending on whether only abduction/adduction or both are affected, DRS has been classified into three types designated as type-I, type-II and type-III. The torsional movements of the affected eye in DRS have not been reported to be deficient hitherto, which could be due to difficulties in the routine bedside evaluation of such movements.Case Presentation An unusual case of a patient of left unilateral type-III DRS is reported, who presented with a short history of vertigo on getting up from supine to sitting position and on assuming right lateral recumbent position. The diagnostic right Dix-Hallpike test (DHT) revealed upbeating torsional geotropic positioning nystagmus in the normal right eye and upbeating positioning nystagmus without torsional component in the abnormal left eye and this clinical finding was video recorded.Conclusion The observed lack of incyclotorsion of the left eye, affected with DRS-III during right Dix-Hallpike positioning, is primarily due to the absence of initial slow-phase excyclotorsional component. If the slow phase of VOR does not occur, then the fast-phase VOR, which is a refixation saccade, will be lacking too. An anastomosis, either in the lateral wall of the cavernous sinus or within the orbit, between the trochlear nerve and fibers of the oculomotor nerve can lead to simultaneous co-contraction of the inferior and superior oblique muscles. This is the most probable explanation for such finding of asymmetrical absence of torsional component in the left eye affected by DRS-III, during right Dix -Hallpike positioning. Thus, the recording of eye movements (voluntary and involuntary) opened a window into the brain to conceptualize neural and mechanical factors influencing the human eye movements.
Keywords: cranial dysinnervation disorder; Dix–Hallpike test; incylotorsional; excyclotorsional; positioning nystagmus; geotropic